1994
DOI: 10.1111/j.1749-6632.1994.tb55795.x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens in the Pathogenesis and Treatment of Alzheimer's Disease in Postmenopausal Women

Abstract: There have been extensive studies documenting the effects of gonadal hormones on behavior in animals (reviewed elsewhere in this symposium and in McEwen et al. ) Sexual behavior in animals is regulated by both "organizational" and "activational" effects of gonadal hormones on the brain. The organizational effects of gonadal hormones are related to those effects on behavior which are the result of gonadal effects on the prenatal development of the brain. These prenatal organizational effects are permanent and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Both prospective and case-control studies have shown that estradiol use in postmenopausal women may decrease the risk of the development and/or expression of AD (Kawas et al, 1997; Paganini-Hill and Henderson, 1994; Panidis et al, 2001; Tang et al, 1996; Zandi et al, 2002) with an overall odds ratio of 0.66 (LeBlanc et al, 2001). Estradiol treatment alone may improve cognitive functioning in some female AD patients (Fillit, 1994; Ohkura et al, 1994) but large controlled trials of estradiol alone as a therapy for mild to moderate AD have been negative, showing no significant effect on cognitive measures of long-term progression (Henderson et al, 2000; Mulnard et al, 2000), although estradiol appears to enhance the effect of anticholinesterase medication in AD (Schneider et al, 1996). It may be that estradiol alone cannot significantly prevent progression of an already established disease, perhaps due to the progressive deterioration in basal forebrain cholinergic systems (Craig et al, 2011) necessary for estrogen to have salutary effects on cognition.…”
Section: Estrogen Studies In Human Cognitionmentioning
confidence: 99%
“…Both prospective and case-control studies have shown that estradiol use in postmenopausal women may decrease the risk of the development and/or expression of AD (Kawas et al, 1997; Paganini-Hill and Henderson, 1994; Panidis et al, 2001; Tang et al, 1996; Zandi et al, 2002) with an overall odds ratio of 0.66 (LeBlanc et al, 2001). Estradiol treatment alone may improve cognitive functioning in some female AD patients (Fillit, 1994; Ohkura et al, 1994) but large controlled trials of estradiol alone as a therapy for mild to moderate AD have been negative, showing no significant effect on cognitive measures of long-term progression (Henderson et al, 2000; Mulnard et al, 2000), although estradiol appears to enhance the effect of anticholinesterase medication in AD (Schneider et al, 1996). It may be that estradiol alone cannot significantly prevent progression of an already established disease, perhaps due to the progressive deterioration in basal forebrain cholinergic systems (Craig et al, 2011) necessary for estrogen to have salutary effects on cognition.…”
Section: Estrogen Studies In Human Cognitionmentioning
confidence: 99%
“…[102,103] Furthermore, it has been claimed that users. [104,105] ERα and ERβ are expressed in the brain and their individual distribution in the rat brain has been evaluated through References the use of in situ hybridization. [106,107] The expression of ERβ in…”
Section: Acknowledgements Estrogenmentioning
confidence: 99%
“…Many clinical studies have supported the therapeutic effect of estrogen on AD, since Fillit et al [20] first reported an open trial of estradiol-17b (E 2 ) therapy for AD (Table 2) [20][21][22][23][24][25][26][27][28][29][30][31][32]. However, the therapeutic effect was not established.…”
Section: ) Therapeutic Effect Of Estrogenmentioning
confidence: 99%